Preparation of Mesoporous SBA-16 Silica-Supported Biscinchona Alkaloid Ligand for the Asymmetric Dihydroxylation of Olefins - Sarkar, Shaheen M.; Md. Eaqub, Ali; Lutfor, M. R.; M. M., Yusoff (Hindawi Publishing Corporation, 2014)
Optically active cinchona alkaloid was anchored onto mesoporous SBA-16 silica and the as-prepared complex was used as a heterogeneous chiral ligand of osmium tetraoxide for the asymmetric dihydroxylation of olefins. The prepared catalytic system provided 90–93% yield of vicinal diol with 92–99% enantioselectivity. The ordered mesoporous SBA-16 silica was found to be a valuable support for the cinchona alkaloid liganded osmium catalyst system which is frequently used in chemical industries and research laboratories for olefin functionalization.